Diet and gut microbiome in gastrointestinal disease. Issue 2 (16th November 2021) - Trakman, Gina L.; Fehily, Sasha; Basnayake, Chamara; Hamilton, Amy L.; Russell, Erin; Wilson‐O'Brien, Amy; Kamm, Michael A.
Abstract: The composition and function of the dynamic microbial community that constitutes the gut microbiome is continuously shaped by the host genome, mode of birth delivery, geography, life stage, antibiotic consumption, and diet. Diet is one of the most potent factors in determining microbiome integrity. Dietary factors in early life appear to substantially determine the risk of later health or disease; for example, exposure to ultra‐processed foods in childhood or adolescence may increase the risk of the later development of inflammatory bowel disease or colorectal cancer, thought to be mediated by modulation of the gut microbiota. Dietary factors when gut diseases are established influence symptoms and disease activity, can form a risk factor for ongoing disease, or can be used as therapy to decrease disease activity. The characterization of dietary content is currently complex and imperfect, but tools are emerging to define precisely the nature of dietary composition. Similarly, the revolution in microbial analysis allows greater understanding of how diet influences microbial composition and function. Defining the interaction between diet, the gut microbiome, and gastrointestinal disease is leading to radical changes in our clinical approach to these disorders.